Optical fiber temperature sensor based on fiber bragg grating - Sadeq Al-musaw, Sadeq Thamer (2018)
It is important to study optical fiber temperature sensor based on fiber Bragg Grating. The Fiber Bragg grating sensors can offer highly sensitive, cost effective solutions for optical sensing. While fiber Bragg gratings have been implemented in various sensing applications over the past few decades, recent efforts explore the limits of reflected and transmitted for FBG sensors. The FBG temperature sensor, is essential to establish the smallest distance of single mode fibre in order to reduce optical losses of the FBG system. One of the most generally used deployed optical sensors is the fiber Bragg grating, with optical circulator, ASE source and OSA, the FBG which reflects a wavelength of light that shifts in response to variations in temperature. The advantage of reflection that its can easily detect the Bragg reflected signal. The FBG is very sensitive to variations in temperature degrees over a temperature range of (30–60) °C. The variation of wavelength of an fiber Bragg grating is caused by the temperature. Moreover, change in temperature affect both the effective refractive and grating period of an FBG, which result in a shift in the reflected wavelength. Moreover, most of the existing FBG sensors systems on the market provide a limited wavelength resolution Therefore, it is the purpose of this thesis to enhance the grating sensors sensitivity to temperature. In addition, the purpose to make a small comparison between the transmitted and reflected spectrum. It is apparent that any shift in the Bragg wavelength is influenced by the temperature. Moreover, the sensitivity was calculated equal to 17.1pm°C with SNR equal to 13.7 dB based on the reflection spectrum.